An internet of things for water utility monitoring and control - Madala, Kranthi; Divya Bharathi, D; Chowdary Polavarapu, Sushma (International Journal of Engineering and Technology, 2018)
The aim of the paper is to advise more efficient water monitoring and control approach to reduce the water loss. This may assist users, operators to improve water control systems, by using the emerging technology. Net of factors is one of the essential strategies for making consumption of water assets more efficient and for developing extra utility proper structures. Now–a–days the water monitoring and control is dealing with a few issues. As an example the manipulate structures used by using water distribution utilities ought to function over a huge vicinity. Massive water utilities go through transit losses due to leaks and burst pipes. An IoT answer for water tracking and control ambitions at being capable of gather more than one device, analyzing these records and dispatching them and consequences from processing to diverse programs or to other devices.